(untitled) (Al-Mashadir: Journal of Quranic Sciences and Tafsir, 2025)
Breastfeeding is a crucial component in child-rearing, which in Islamic perspective is not only viewed as a biological necessity but also carries spiritual and ethical significance. This study aims to examine the command of breastfeeding in the Qur’an, particularly the use of the term al-radhā‘a and the prescribed duration of two years, and to explore its relevance to modern health science findings. The research employs a thematic interpretation method (tafsīr mawḍū‘ī) by collecting and analyzing Qur’anic verses related to breastfeeding, such as Surah Al-Baqarah [2]: 233, Surah Luqman [31]: 14, and Surah Al-Ahqaf [46]: 15. These verses are then examined through an interdisciplinary approach alongside modern medical literature discussing the benefits of breast milk. The findings indicate that the Qur’anic recommendation of a two-year breastfeeding period aligns with contemporary medical advice, which supports exclusive breastfeeding for the first six months, followed by continued breastfeeding up to two years. Scientifically, breast milk contains essential nutrients and antibodies that are vital for optimal growth and immune development in infants. This study concludes that the Qur’anic guidance on breastfeeding reflects divine wisdom that is consistent with modern scientific understanding. Therefore, it is essential to raise awareness among Muslims to regard breastfeeding as an integral part of implementing religious teachings that contribute to raising a healthy, strong, and morally upright generation.